Vanuatu's Typical Approach of Mathematics vs the TUAM Approach of Mathematics - Kency Obed SAWAH (Southeast Asian Mathematics Education Journal, 2022)
There are multiple factors contributing to the low level of mathematics in basic education in the Republic of Vanuatu. Results through the Vanuatu Standard Test of Achievement (VANSTA) in 2017 and 2019 unveiled that there were gaps in the performance of mathematics which cause the overall achievement to stagnant which were below the expected minimum standard (Curriculum Development Unit, 2020). This study investigated the current situation of the teaching mathematics approach in the country recognised as the ‘I Do-We Do-You Do’ teaching model. In comparison, the study also examined the influence of the ‘Try-Understand-Apply-Master’ (TUAM) discovery learning process on students in Vanuatu. The study compared these two teaching approaches through pre and post-test interventions among the control and experimental group of two grade five classes. The findings of the study discovered a possibility that the TUAM discovery learning process could be effective in improving the mathematics level in the basic education in the Republic of Vanuatu.